+0  
 
0
259
2
avatar

(sec(x)-1) * (sec(x)+1)* cot(x) = tan(x)

Guest Jun 13, 2017
 #1
avatar
+1

use the identity (a+b)(a-b) = a^2  - b^2  with {(sec x)-1}{ (sec x +1) }   to get

sec^2(x)  -  1

we can now write expression as

{sec^2(x) -1} * cot (x)    

and use the trig identity  sec^2(x) - 1   = tan^2(x)    to get expression as

tan^2(x)*cot(x)   = tan^2(x) * {1/tan(x)}     = tan(x)

Guest Jun 13, 2017
 #2
avatar+7023 
+2

\(\text{LHS}\\ =(\sec x - 1)(\sec x + 1)(\cot x) \\ =(\sec^2 x - 1)(\cot x)\\ =(\tan^2 x)(\cot x)\\ =\tan x\\ =\text{RHS}\)

MaxWong  Jun 13, 2017

11 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.